The role of artificial intelligence utilization and digital literacy in independent learning - Gani, Imam Prawiranegara; Ardiansyah; Mohehu, Fazri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study analyzes the roles of artificial intelligence utilization and digital literacy in students' independent learning in the Economics Education Department, Faculty of Economics and Business, Gorontalo State University. Using a quantitative, explanatory research design, data were collected via questionnaires distributed to 234 respondents. The respondents were selected using proportional stratified random sampling by generational group. The data were analyzed using multiple linear regression in SPSS 24. The findings indicate that the utilization of artificial intelligence and digital literacy has been proven to have a simultaneous and significant impact on students' independent learning. Digital literacy has a more dominant influence than artificial intelligence, as indicated by higher Beta coefficient values and t-statistic. The implications of this research are the importance of utilizing artificial intelligence and of strengthening digital literacy in the curriculum and learning strategies, creating a higher education ecosystem that is adaptive, innovative, and supports students as independent learners in the digital age.